THE COMPARATIVE ANALYSIS OF PROFITABILITY INDICATORS OF COMPANIES BEFORE AND AFTER THE IMPLEMENTATION OF INVESTMENT PROJECTS WITH NON-REFUNDABLE FINANCING - CENAR, Iuliana; TURCAS, Mioara (Annales Universitatis Apulensis Series Oeconomica, 2014)
The overall objective of the research is a comparative analysis of profitability indicators of companies in Alba before and after investment projects were implemented with nonrefundable financing. As the research involved companies with production activity and service providing, the indicators that are targeted are the ones that imply permanent capital. The research methodology was based on the documentation and the archive study of the balance sheet and the financial statements of the companies that were surveyed, the case study method and the comparison of the data before and after the implementation of investment projects with nonrefundable financing. The results of the research reflect the importance of permanent capital acquisition in order to ensure the performance of the company.